Sustaining Malaysia’s rice economy: the role of economic drivers in food security - Rozaimah Zainudin; Adilah A. Wahab; Elya Nabila Abdul Bahri (Penerbit Universiti Kebangsaan Malaysia, 2025)
Food security has consistently been a strategic goal for Malaysia, specifically given its dependence on imported food, diminishing agricultural land, and evolving agricultural policies. This study examines the impact of Malaysia’s National Agricultural Policies, food export, food import, and agricultural land on food security. The study employs time-series data from 1964 to 2021. Using the autoregressive distributed lag-error correction model, the findings reveal that food import, agricultural land, 1st-3rd Malaysia Plan, and 3rd National Agricultural Policies exhibit long-run relationships with food security, while food export and food import adjust to equilibrium more rapidly than agricultural land. This study also investigates the interaction effects of National Agricultural Policies, and indicate that 3rd and 4th National Agricultural Policies strengthen the influence of food export and food import on food security, whereas 1st-3rd Malaysia Plan, and 3rd National Agricultural Policies moderate the relationship between agricultural land and food security. This research contributes to the literature by linking modernisation theory to policy outcomes and employing the autoregressive distributed lag-error correction model, which remains underutilized in food security studies. The policy implications of this study suggest that policymakers should consider formulating a new National Agricultural Policy by incorporating effective strategies from the 1st-3rd Malaysia Plans, as well as the 3rd National Agricultural Policy. Priority should be given to modernising the agro-food industry to enhance food production, while also addressing the dynamics of food exports and imports to strengthen Malaysia’s overall food security.